الكفايات الضرورية للمشرفين التربويين ومدى ممارستها وفق معايير الجودة الشاملة من وجهة نظر المشرفين التربويين والمعلمين بسلطنة عمان :‏ ‏محافظة شمال الباطنة أنموذجا /‏ - جابري، خالد محمد (Kulliyyah of Education, International Islamic University Malaysiah, 2014)
This study aims at determining the necessary competencies for educational supervisor in accordance with measures of total quality management (TQM), and the extent to which educational supervisors practice them from the perspectives of teachers and educational supervisors in the province of al-Batinah North in the Sultanate of Oman. The study sampled 22 educational supervisors and 257 teachers for data collection. A mixed-methods approach was used. Quantitatively, a descriptive survey technique was used. Qualitatively, the study interviewed educational supervisors and distributed survey questionnaires to teachers for data collection. The findings yielded that educational supervisors in the Province of al-Batinah North highly practise the necessary competencies in accordance with TQM measures to carry out their day-today responsibilities. However, engaging in such practices per se does not guarantee achieving expected aspirations, therefore a careful attention should be rendered to improving performance of educational supervisors. The study discloses statistical significant differences of gender and experience on performance of educational supervisors (α = ≤ 0.05). Furthermore, the analysis however revealed insignificant effect for level of education on respondents' performance (α = ≥ 0.05).